2013
DOI: 10.1016/j.jnutbio.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term vitamin A deficiency induces alteration of adult mouse spermatogenesis and spermatogonial differentiation: direct effect on spermatogonial gene expression and indirect effects via somatic cells

Abstract: The objective of this study was to further understand the genetic mechanisms of Vitamin-A-Deficiency (VAD) induced arrest of spermatogonial stem-cell differentiation. Vitamin A and its derivatives (the retinoids) participate in many physiological processes including vision, cellular differentiation and reproduction. VAD affects spermatogenesis, the subject of our present study. Spermatogenesis is a highly regulated process of differentiation and complex morphologic alterations that leads to the formation of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…However, although there is a small amount of evidences about the long-term effects of VAE on rat spermatogenesis, previous studies focused on the effects on body and reproductive organ weights, which have not been previously well characterized (Lamano Carvalho et al, 1978;Bosakowski et al, 1988). The present study was conducted to investigate whether long-term intake of VAE arrested spermatogenesis in mice, and it demonstrated for the first time the molecular mechanism of spermatogenic arrest, which was partly different from that in vitamin A-deficient mice as reported previously (Boucheron-Houston et al, 2013). The vitamin A intake (1,000 IU/g diet) in the present study was lesser than in previous reports (Bosakowski et al, 1988) and could not cause teratogenicity (10,000 IU/day) (Miller et al, 1998).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, although there is a small amount of evidences about the long-term effects of VAE on rat spermatogenesis, previous studies focused on the effects on body and reproductive organ weights, which have not been previously well characterized (Lamano Carvalho et al, 1978;Bosakowski et al, 1988). The present study was conducted to investigate whether long-term intake of VAE arrested spermatogenesis in mice, and it demonstrated for the first time the molecular mechanism of spermatogenic arrest, which was partly different from that in vitamin A-deficient mice as reported previously (Boucheron-Houston et al, 2013). The vitamin A intake (1,000 IU/g diet) in the present study was lesser than in previous reports (Bosakowski et al, 1988) and could not cause teratogenicity (10,000 IU/day) (Miller et al, 1998).…”
Section: Discussionmentioning
confidence: 56%
“…In normal mice testes, the cellular localization of these retinoid receptors has been exclusively studied by in situ hybridization and immunohistochemical analysis (Vernet et al, 2006). Rarβ and Rxrγ mRNA expressed in step 7 and 8 round spermatids (Vernet et al, 2006) in the testes were decreased by VAE intake, identical to the changes induced by vitamin A deficiency (Boucheron-Houston et al, 2013). These results suggested that excess of vitamin A or its deficiency in mice resulted in decreased differentiation of step 7 and 8 round spermatids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigating the consequences of VAD in the testes also found that spermatogenesis is dependent on vitamin A availability. Of note, effect of dietary vitamin A deprivation did manifest at a much later time point in the previous study (42). Thus, STRA6 seems to provide a fail-safe mechanism to protect spermatogenesis and ensure the production of progeny even when vitamin A is in short supply.…”
Section: Discussionmentioning
confidence: 57%
“…For example, diet-induced obesity and vitamin D or zinc deficiency can lead to a decrease in male fertility in mice (Fan et al 2015; Sun et al 2015; Croxford et al 2011). Adult mice deprived of dietary vitamin A show testicular degeneration as a result of increased apoptosis and sloughing of immature germ cells into the lumen in more severe cases (Boucheron-Houston et al 2013). Several of these observations have parallels in humans: obese men are more likely to be infertile (Campbell et al 2015), and there is a positive correlation between vitamin D and zinc and sperm quality in adult men (Blomberg Jensen 2014; Colagar et al 2009).…”
Section: Responses Of Germline Stem Cell Lineages To Dietmentioning
confidence: 99%